Clinical significance of WES-defined ERBB2 amplification in resectable colorectal cancer - Kazuki Kishi; Atsushi Hamabe; Yusuke Suwa; Naoya Akazawa; Keiji Hirata; Masataka Ikeda; Mitsuru Yokota; Kentaro Kato; Masahito Kotaka; Yujiro Nishizawa; Hideaki Bando; Yoshiaki Nakamura; et al. (International Journal of Clinical Oncology, 2026)
Abstract Background HER2 amplification is demonstrated to influence response to therapy and outcomes in metastatic colorectal cancer (mCRC), but its role in resectable CRC remains unclear. This study investigated the prognostic impact of WES-defined ERBB2 amplification and its association with adjuvant chemotherapy (ACT) efficacy and circulating tumor DNA (ctDNA) in resectable CRC. Methods Data from 3607 patients with resectable CRC from the GALAXY study were analyzed. HER2 amplification was defined using ERBB2 copy number alterations based on whole exome sequencing of tumor specimens. We analyzed disease-free survival (DFS) in WES-defined ERBB2 amplified CRC, evaluating ACT benefit and the correlation between ERBB2 copy number and ctDNA status. Results No significant difference in DFS was observed between those with and without WES-defined ERBB2 amplification in a univariate ( P = 0.0659) or a multivariate analysis ( P = 0.2300). Among patients with pathological stage III, ACT was associated with improved DFS in the non-amplified subgroup (HR 0.67, P = 0.0002), particularly in the subgroup of patients with early post-operative (2–10 weeks following surgical resection) ctDNA-positivity (HR 0.27, P < 0.0001), whereas no clear association was detected in the small amplified subgroup; however, the ACT-by- ERBB2 amplification interaction was not statistically significant. While WES-defined ERBB2 amplification correlated with higher early post-operative ctDNA positivity ( P = 0.0486), ERBB2 copy number did not associate with recurrence or levels. However, early post-operative ctDNA positivity strongly predicted poor DFS in patients with WES-defined ERBB2 amplification (HR 15.26, P < 0.0001). Conclusions WES-defined ERBB2 amplification was not identified as a significant adverse prognostic factor in resectable CRC, unlike early post-operative ctDNA status. The limited number of amplified cases precluded a reliable assessment of whether WES-defined ERBB2 amplification modifies the association between ACT and DFS.